Individual’s awareness of his personal relationships with other members of the Group - Zhubanazarova, N. S.; Dzhakupov, S. M.; Pahratdinova, B. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2013)
The problem of character of typology is considered, data of long-term researches of individual styles of self-regulation at the different types of personality accentuations of character are generalized. Regulator basis and style forming role of subjective internals of personality (to responsibility, persistence, independence, flexibility of and other) are described. It is shown that efficiency of individual self-regulation depends not only on the type of accentuation, how many from development of personality of subject internals combination of that is specific for the different types of char-acter. Besides, the content of that concept includes formal representation of the relationship that binds the object and the subject of perception. In the most general terms, we can say that the perception of another person means the perception of his external features, their correlation with the personal characteristics of the individual perceived and interpretation on this basis of his actions.